2009
DOI: 10.1021/ja9083978
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Peptide Channels and Encapsulated Water Wires

Abstract: Peptide nanotubes with filled and empty pores and close-packed structures are formed in closely related pentapeptides. Enantiomorphic sequences, Boc-(D)Pro-Aib-Xxx-Aib-Val-OMe (Xxx = Leu, 1; Val, 2; Ala, 3; Phe, 4) and Boc-Pro-Aib-(D)Xxx-Aib-(D)Val-OMe ((D)Xxx = (D)Leu, 5; (D)Val, 6; (D)Ala, 7; (D)Phe, 8), yield molecular structures with a very similar backbone conformation but varied packing patterns in crystals. Peptides 1, 2, 5, and 6 show tubular structures with the molecules self-assembling along the crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 74 publications
2
43
0
1
Order By: Relevance
“…Their results agree with Engels et al (1995) who also state that the water molecules prefer to be in the free space between each peptide ring. However, results of Song et al (2013), Liu et al (2010), Engels et al (1995) contradict the findings of Raghavender et al (2009Raghavender et al ( , 2010) that in tubes with diameters ranging from 5.2 to 7.7 Å , water molecules align in a single file along the long axis of a peptide nanotube.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Their results agree with Engels et al (1995) who also state that the water molecules prefer to be in the free space between each peptide ring. However, results of Song et al (2013), Liu et al (2010), Engels et al (1995) contradict the findings of Raghavender et al (2009Raghavender et al ( , 2010) that in tubes with diameters ranging from 5.2 to 7.7 Å , water molecules align in a single file along the long axis of a peptide nanotube.…”
Section: Introductionmentioning
confidence: 82%
“…7). By considering this, we are able to predict whether the equilibrium arrangement of the water molecules inside the peptide nanotube will be a single file as seen in Raghavender et al (2009Raghavender et al ( , 2010 or a 1 À 2 À 1 À 2 file as suggested by Engels et al (1995), Song et al (2013), Liu et al (2010). In this section, we assume that the peptide nanotube only comprises two peptide units.…”
Section: Interaction Of Two Water Molecules Inside a Cyclic Peptide Nmentioning
confidence: 96%
“…Molecules confined inside nanoscale space such as narrow nanotubes or membrane proteins can form one-dimensional (1D) molecular wires, which have attracted intense interest recently because of their scientific importance and potential applications in nanotechnology [1,21,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. Among them, it is of particular interest in determining the structure and dynami-cal behavior of water wires [1,21,[40][41][42][43][44][45][46][47][48][49] which have been found to exist in narrow nanotubes [1,21,[40][41][42][46][47][48] and biological channels [43][44][45].…”
Section: Molecular Wire Of Urea Inside Narrow Carbon Nanotubementioning
confidence: 99%
“…Among them, it is of particular interest in determining the structure and dynami-cal behavior of water wires [1,21,[40][41][42][43][44][45][46][47][48][49] which have been found to exist in narrow nanotubes [1,21,[40][41][42][46][47][48] and biological channels [43][44][45]. Water wires have many interesting properties, such as wavelike density distributions [1,46], rapid and concerted motions [1,40,43], orientation-ordered structures and collective flips [1,21,41,48], and excellent on-off gating behaviors [46,47].…”
Section: Molecular Wire Of Urea Inside Narrow Carbon Nanotubementioning
confidence: 99%
See 1 more Smart Citation